ISLAMIC PERSPECTIVE OF ENHANCING ECONOMIC DEVELOPMENT FOR MARITIME COMMUNITIES IN INDONESIA - Rosita Tandos (El-Qist: Journal of Islamic Economics and Business (JIEB), 2014)
Developing maritime area and sector is a important strategy for the development of Indonesia although many challenges exist to achieve this goal. On the other hand, women as a crucial element of society have play important roles in family and community lives. Such contribution could affect the development processes of the maritime area and the country.Islamic banking and other institutions that have community economic programs can implement principle of creating prosperity and justice to the life of people though conducting a community economic development (CED) program that reflect more to the aspiration, need and insterest of the people. These all attempts are significant to support the current development policies of the Indonesian governments that emphasize on strengthening maritime area and resources.